ANALISIS KEPUASAN KERJA PEGAWAI BAGIAN TATA USAHA PADA RUMAH SAKIT DAERAH RADEN MATTAHER JAMBI - Adnan Khasogi H. (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2015)
The purpose of this study was to describe job satisfaction at Raden Mattaher General Hospital Jambi. The method used in this study is a Quantitative Approach, namely data collected through a survey method with a structured list of questions. Based on the data collected in this way, it will be possible to explain the description of employee job satisfaction at Raden Mattaher Hospital, Jambi Province. The results of this study indicate that the seven indicators that affect employee satisfaction at the Raden Mattaher General Hospital in Jambi Province must be further improved so that good satisfaction is realized, because of the seven indicators of fair and proper remuneration, placement according to expertise, the severity of the work, the atmosphere and work environment, the equipment that supports the implementation of the work, the attitude of the leader in his leadership, the nature of the work is monotonous or not, only one thing that does not affect satisfaction is the lightness of the work indicator. The suggestion of this research is that the leadership of the Raden Mattaher Hospital in Jambi Province must be optimal in applying satisfaction factors to their employees so that they can work as they should and can increase work loyalty.